Antibacterial activities of Calendula officinalis callus extract - Burcu Çetin; Fatih Kalyoncu; Betül Kurtuluş (International Journal of Secondary Metabolite)
The purpose of this study was to determine the antibacterial activity of C. officinalis callus derived from cotyledon explants. Cotyledons excised from in vitro germinated seedlings were used as explants. Explants were transferred on MS medium supplemented with benzil amino purine (BAP; 2 mg l-1), α-naphthalene-acetic acid (NAA; 2 mg l-1) for callus studies. The cultures were maintained on the same media compositions and were sub-cultured at an interval of 4 weeks. Callus cultures were harvested at the end of the 16th week. Calli were dried at 40̊ C in the dark for antimicrobial studies. Calendula officinalis callus extracts were tested for their antibacterial activities by using agar well diffusion method. Ethanol and chloroform extracts from these plants were assayed against nine bacteria species (Staphylococcus aureus ATCC 6538, Escherichia coli ATCC 25922, Bacillus cereus ATCC 7064, Bacillus subtilis ATCC 6633, Salmonella typhimurium CCM 5445, Proteus vulgaris ATCC 6896, Enterococcus faecalis ATCC 29212, Enterobacter cloacae ATCC 13047, and Kocuria rhizophila ATCC 9341). The test antibiotics penicillin G, novobiocin, amphicillin, chloramphenicol and erythromycin were used for comparison. Callus formation was observed at the end of the 5th week on cotyledon explants. C. officinalis callus extracts showed 38 mm inhibition zone against S. aureus, and chloroform extracts showed 32 mm inhibition zone against B. cereus. These results are very close to the test antibiotics used and C. officinalis is found more effective on gram positive bacteria.